Trajectory Planning of the Humanoid Manipulator - C. Kacprzak; G. Pająk (International Journal of Applied Mechanics and Engineering, 2019)
The paper presents a method of planning a collision-free trajectory for a humanoid manipulator mounted on a rail system. The task of the robot is to move its end-effectors from the current position to the given final location in the workspace. The method is based on a redundancy resolution at the velocity level. In addition to this primary task, secondary objectives are also taken into account. The motion of the robot is planned in order to maximize a manipulability measure in purpose of avoiding manipulator singularities. State inequality constraints resulting from collision avoidance conditions are also considered. A computer example involving a humanoid manipulator operating in a three dimensional task space is also presented.